Collagen-1 and elastin expression in cervical tissue: A comparison across cervical elongation, pelvic organ prolapse, and combined conditions - Anis Widyasari; Gatut Hardianto; Etty Hari Kusumastuti; Eighty Mardiyan Kurniawati (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS